Polymeric Adsorbent for the Effective Removal of Toxic Dyes from Aqueous Solutions: Equilibrium, Kinetic, and Thermodynamic Modeling - Oter, Cigdem; Gokkus, Kutalmis; Gur, Mahmut; Butun, Vural (Wiley, 2024)
Abstract This study investigates the adsorption behavior of anionic (Congo red, Eosin yellow) and cationic (Malachite green) dyes on synthesized TD polymer particles, highlighting the material's potential as an effective adsorbent for industrial wastewater treatment. Key operational parameters, including initial solution's pH, contact time, initial dye concentration, and temperature, were systematically evaluated to determine their influence on adsorption efficiency. The experimental data demonstrated that the Langmuir isotherm provided the best fit for all three dyes, indicating monolayer adsorption with maximum adsorption capacities of 153.8 mg/g for Malachite green, 49.36 mg/g for Congo red, and 227.9 mg/g for Eosin yellow. Kinetic analysis revealed that the adsorption of Malachite green and Congo red followed pseudo‐second‐order kinetics, while Eosin yellow adsorption was better described by the intra‐particle diffusion model. Thermodynamic assessments, including Gibbs free energy (Δ G °), enthalpy (Δ H °), and entropy (Δ S °), confirmed the spontaneous and endothermic nature of the adsorption processes for Malachite green and Eosin yellow, contrasting with the exothermic behavior observed for Congo red. These findings underscore the versatility and effectiveness of TD polymer particles in removing both anionic and cationic dyes from aqueous solutions. Further research could explore material optimization and real‐world applications to broaden their utility in sustainable water treatment strategies.